Sosialisasi Tentang Relaksasi Otot Progresif Pada Penderita Batu Ginjal Di Poli Urologi Rumah Sakit TK III Dr R Soeharsono Banjarmasin - Ariani, Sri Purwanti; Sri Jamilah; Yuhansyah; Sarifa (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
Kidney stone remains one of the most common health problems in urology worldwide, including in Indonesia. Patients with kidney stones have hard, crystalline masses along the urinary tract, causing pain. Progressive muscle relaxation and deep breathing techniques are aimed at reducing muscle tension and anxiety to prevent an increase in pain stimuli, serving as one of the methods for managing acute pain. The purpose of this study was to determine whether progressive muscle relaxation can reduce pain in patients with right kidney stones. This research utilized a case study approach with nursing care intervention. The Numeric Rating Scale (NRS) was used to measure pain. The study included patients with kidney failure. Assessment, diagnosis, treatment, implementation, and evaluation were all part of the collected data. The intervention performed was progressive muscle relaxation therapy conducted three times a day on Tuesday. The research findings indicated that progressive muscle relaxation mediated a decrease in patient discomfort scale, with the outcomes including reduced expressions of pain, anxiety, difficulty resting, and groaning, shifting from moderate to mild. Patients no longer complained of pain and showed a decrease in pain.